Changes in mRNA/protein expression and signaling pathways in in vivo passaged mouse ovarian cancer cells. - Qingchun Cai; Qipeng Fan; Aaron Buechlein; David Miller; Kenneth P Nephew; Sheng Liu; Jun Wan; Yan Xu (PLoS ONE, 2018)
The cure rate for late stage epithelial ovarian cancer (EOC) has not significantly improved over several decades. New and more effective targets and treatment modalities are urgently needed. RNA-seq analyses of a syngeneic EOC cell pair, representing more and less aggressive tumor cells in vivo were conducted. Bioinformatics analyses of the RNA-seq data and biological signaling and function studies have identified new targets, such as ZIP4 in EOC. Many up-regulated tumor promoting signaling pathways have been identified which are mainly grouped into three cellular activities: 1) cell proliferation and apoptosis resistance; 2) cell skeleton and adhesion changes; and 3) carbohydrate metabolic reprograming. Unexpectedly, lipid metabolism has been the major down-regulated signaling pathway in the more aggressive EOC cells. In addition, we found that hypoxic responsive genes were at the center stage of regulation and detected functional changes were related to cancer stem cell-like activities. Moreover, our genetic, cellular, biochemical, and lipidomic analyses indicated that cells grown in 2D vs. 3D, or attached vs. suspended had dramatic changes. The important clinical implications of peritoneal cavity floating tumor cells are supported by the data proved in this work. Overall, the RNA-seq data provide a landscape of gene expression alterations during tumor progression.